Mucinous Cystadenoma Arising in a Mature Cystic Teratoma in a 25-Year-Old Patient - Michelle D. Pintea (Case Reports in Obstetrics and Gynecology)
Coexistence of a mucinous cystadenoma arising in a mature cystic teratoma is infrequently reported. Herein a case of a 25-year-old woman diagnosed with a right ovarian mucinous cystadenoma arising in a mature cystic teratoma is reported. She presented with lower right abdominal discomfort. Ultrasound showed a 14.8×7.9×12.5 cm structure on the right adnexa. She underwent a diagnostic laparoscopy, which was converted to exploratory laparotomy, during which a right salpingo-oophorectomy was performed.